2010
DOI: 10.3192/jsirib.25.1
|View full text |Cite
|
Sign up to set email alerts
|

Effective Treatment for Recurrent Pregnancy Loss

Abstract: Abstract:Understanding the etiology of recurrent pregnancy loss (RPL) has been increasing in importance in reproductive medicine, especially in societies with low birth rates. Since the cause of human miscarriage is often complicated and multifactorial, effective treatment for the successful maintenance of pregnancy requires the comprehensive clinical management of recurrent wastages. Immunology for the maintenance of pregnancy is a very attractive field; however, the role of immunology during human gestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The control group consisted of 47 randomly selected women with congenital uterine anomalies not treated by metroplasty. This study revealed that 152 out of 161 subsequent pregnancies (94.4%) terminated in spontaneous abortion [30]. Thus, metroplasty for the treatment of septate uterus appears to be an appropriate surgical intervention with the ability to improve the subsequent reproductive outcome.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The control group consisted of 47 randomly selected women with congenital uterine anomalies not treated by metroplasty. This study revealed that 152 out of 161 subsequent pregnancies (94.4%) terminated in spontaneous abortion [30]. Thus, metroplasty for the treatment of septate uterus appears to be an appropriate surgical intervention with the ability to improve the subsequent reproductive outcome.…”
Section: Discussionmentioning
confidence: 86%
“…Ayhan et al [29] evaluated the reproductive performance of 102 patients who underwent conventional metroplasty for the treatment of septate uterus and reported that the miscarriage rate was reduced from 90% before surgery to 17% after abdominal metroplasty. In our recent statistical data [30], we performed modified metroplastic surgery in 173 women: 101 with septate uterus, 59 with arcuate uterus, 10 with a T-shape uterus and 3 with a double uterus. As demonstrated in this study, the subsequent reproductive outcome was distinctly improved, with a reduction in the miscarriage rate from 93.2% to 12.5%, and an increase in the term delivery rate from 1.3% to 63.4%.…”
Section: Discussionmentioning
confidence: 99%